Meteorological and Air Quality Models for Urban Areas - Baklanov, Alexander.; Sue, Grimmond.; Alexander, Mahura.; Athanassiadou, Maria. (Springer Berlin Heidelberg, 2009)
This book, based on the selected presentations given at the COST728 workshop, is concerned with the following main topics/chapters: 1. Urban morphology and databases, 2. Parameterisations of urban canopy, 3. Strategy for urbanization of different types of models, 4. Evaluation and city case studies / field studies. The chapters were concerned with dynamic (on wind and turbulent) and thermal effects (on temperature and energy in general). The final chapter of this volume summarizes the discussion and conclusions from the four main topics and provides recommendations and future requirements. The book is oriented towards numerical weather prediction and air quality modelling communities.